Beyond 1000 nm Emission Wavelength: Recent Advances in Organic and Inorganic Emitters for Deep‐Tissue Molecular Imaging - Ding, Feng; Fan, Yong; Sun, Yao; Zhang, Fan (Advanced healthcare materials, 2019)
In vivo second near‐infrared (NIR‐II, 1.0–1.7 µm) bioimaging , a rapidly expanding imaging tool for preclinical diagnosis and prognosis, is of great importance to afford precise dynamic actions in vivo with high spatiotemporal resolution, deeper penetration, and decreasing light absorption and scattering. In the course of preclinical practices, organic and inorganic emitters with NIR‐II signals are indispensable keys to open the invisible biological window. In this review, NIR‐II emitters, including but not limited to organic emitters like organic small molecules and copolymers, and inorganic emitters such as lanthanide‐based nanocrystals, quantum dots like Ag2S dots, and carbon nanotubes, are described, especially regarding their unique optical features and noteworthy functions for animal bioimaging. Along with these existing advances, the challenges and potential spaces for further progress are discussed to offer an approximate direction for future researches. In vivo second near‐infrared bioimaging is of great importance to provide precise information with high temporal and spatial resolution and deeper penetration depth. In this mini review, NIR‐II contrast agents including organic and inorganic materials are described with respective features and unique optical functions for animal bioimaging. Later, the challenges and potential spaces for further progress are also discussed.